PENGARUH LATIHAN DEPTH JUMP TERHADAP DAYA LEDAK OTOT TUNGKAI ATLET BOLAVOLI - zulbahri Arrahman (JURNAL PENDIDIKAN ROKANIA, 2017)
This study aims to determine the effect of depth jump exercises on the muscle limb power of athlete volleyball Lintau asset. This research is a quasi-experimentalresearch. Population in this research, which is athlete of volleyball of Lintau Asset which amount 35 people. The sampling was done by purposive sampling with 20 persons. Data retrieval is done by vertical jump test. Data analysis and hypothesis testing of research using t-test with significant level α = 0,05. The result of data analysis showed that there is an effect of depth jump exercise on explosive muscle power of athlete bolavoli Lintau asset with titung (2.73)> ttable (1,729), and also increase of explosive ability of leg muscle from 78.4 average to 79.9.